(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2003)
Verbal Behavior (1957), by B. F. Skinner, provides an innovative analysis of verbal behavior. This article presents and demonstrates some of the concepts and processes included in this work on the functional analysis of verbal behavior, such as: the concept and kinds of verbal behavior within a functional analysis and their organization, multiple causation, the role of the listener (audience), verbal thought, the verbal community, conscience, among others. Daily and literary verbal behavior are used as examples. Some of the questions that have been researched in the area of verbal behavior, as well as some of the specific difficulties of its study, are briefly mentioned and discussed.